2016
DOI: 10.1515/pjfns-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity of a Turkish Traditional Alcoholic Drink, Raki

Abstract: Raki is an aniseed fl avoured traditional Turkish alcoholic drink. Antioxidant capacity of raki samples from different commercial brands were evaluated by CUPRAC, DPPH, TEAC and ORAC assays and correlations between these assays and total phenolic content were also investigated. Additionally, the one-way ANOVA and Bonferroni tests were performed to compare differences between values of the samples. Results indicated that different raki samples exhibited different antioxidant capacity and total phenolic content.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The same authors found that homemade rums and aged distillates were best correlated, followed by bitter liqueurs, fruit liqueurs and bitters. Significant correlations of raki samples TPC with CUPRAC, TEAC and ORAC (0.8071, 0.8196 and 0.7998, respectively) indicated that phenolic compounds might be among the main components responsible for free radical scavenging ability (Yalcin 2016). Polarographic AO assay based on hydrogen peroxide scavenging (HPS), as well as DPPH and total phenolics for various red and white wines of different origin and various spirits, were strongly correlated (r 2 [ 0.95) (Gorjanović et al 2010a, b).…”
Section: Antioxidant Activity Of Obtained Liqueur and Comparison Withmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors found that homemade rums and aged distillates were best correlated, followed by bitter liqueurs, fruit liqueurs and bitters. Significant correlations of raki samples TPC with CUPRAC, TEAC and ORAC (0.8071, 0.8196 and 0.7998, respectively) indicated that phenolic compounds might be among the main components responsible for free radical scavenging ability (Yalcin 2016). Polarographic AO assay based on hydrogen peroxide scavenging (HPS), as well as DPPH and total phenolics for various red and white wines of different origin and various spirits, were strongly correlated (r 2 [ 0.95) (Gorjanović et al 2010a, b).…”
Section: Antioxidant Activity Of Obtained Liqueur and Comparison Withmentioning
confidence: 99%
“…Taking into account that metabolism of alcohol leads to the production of hydroxyl radicals associated with potential liver damage (Albano 1996), natural AOs present in alcoholic beverages might be of special importance. Phenolic compounds extractable with a mixture of alcohol and water, present in various alcoholic beverages, including liqueurs, have attracted increasing attention, particularly with respect to the free radicals scavenging ability (Imark et al 2000;Lee et al 2005;Alamprese 2005;Paixao et al 2007;Gorjanović et al 2010a, b;Li and Beta 2011;Mrvcic et al 2012;Yalcin 2016). Therefore, although alcoholic drinks cannot be classified as functional beverages, herbal spirits may be considered to exhibit functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction in Raki exhibited slightly lower conversion (83%), perhaps due to the presence of phenolic antioxidants derived from anise. 31 As a category, polymerizations in darker liquors (including Scotch whisky, bourbon, Irish whiskey, bask, and Cognac) showed slightly lower conversion than those in lighter liquors, with similarly low dispersity (68−88% conversion, Đ ≤ 1.1; Figures S7 and S8). Of these Jeppson's Malort had the lowest conversion (68%), suggesting flavonoid or lignin compounds extracted from wormword impact polymerization efficacy.…”
Section: Acs Macro Lettersmentioning
confidence: 98%
“…The use of colorless unflavored liquors (i.e., vodka, tequila, and gin) afforded high monomer conversion with narrow dispersity (88–95% conversion, Đ ≤ 1.2; Figures S5 and S6). The reaction in Raki exhibited slightly lower conversion (83%), perhaps due to the presence of phenolic antioxidants derived from anise …”
mentioning
confidence: 99%
“…However, taking other components into consideration, authors claim that for both SET-LRP and RAFT mechanisms, the presence of antioxidants may be unfavourable to the mechanism applied, 14,36 which is the reason for lower conversion of NIPAM in Raki, 36 containing phenol compounds from anise. 191 In ATRP, on the other hand, antioxidants play the role of reducing factors, regenerating the active form of catalyst, and providing a constant concentration of propagating radicals, 3 thus the presence of sugars or coumarin aromatic derivatives in flavoured vodka 192 accelerated the growth of PDMAEMA significantly comparing to other "pure" vodkas (k app p approximately twice higher). 64 Another group of drinks is darker liquors such as whiskey, bourbon, or brandy, in which the alcohol content is similar to that in vodkas.…”
Section: Alcoholic Drinks As a Source Of Reducing Factorsmentioning
confidence: 99%